Penggunaan HCl Sebagai Leaching Agent Dan Pengaruh Penambahan H2O2 Pada Desulfurisasi Green Coke - Mawardi Anwar; Zul Afkar; Dekna Aswita (Jurnal Periodic Jurusan Kimia UNP, 2013)
Desulfurization research on green coke of Refinery Unit II Dumai production with 0.44% sulfur content has been done. The purpose of this research is to study the performance of leaching  method on green coke desulfurization and find out the effect of HCl concentration, stirring time and the effect of the addition of H2O2 to the green coke desulfurization. In this study obtained the optimum concentration of HCl as the leaching agent is 9 M. The results showed that the stirring time of 60 minutes and 9 M HCl concentration, levels of sulfur that can be separated is 3.58%. Then conducted leaching at the optimum conditions with the addition of 6% H2O2.  Levels of sulfur that can be separated by the addition of H2O2 is 3.68%. In this research, the addition of H2O2 increased  percent of desulfurization.